Monolithic scalable compliant mechanisms - Jared R. Hunter; Bethany Parkinson; Jacob L. Sheffield; Mark B. Rober; Brian D. Jensen; Spencer P. Magleby; Nathan S. Usevitch; Larry L. Howell (PLoS ONE, 2026)
Scaling a physical device’s geometry results in mechanical properties changing in various ways (e.g. the cubed-squared law states that for a scaling factor C , mass scales with C 3 and surface area with C 2 ). These scaling effects can result in a device’s inconsistent and unplanned mechanical behavior when varying its fabricated size, thereby necessitating unique designs at different scales. We show that for displacement-driven compliant mechanisms, mechanical stress is uniquely invariant with scale. This effect is described theoretically, verified through computer models and physical testing, and is demonstrated in three examples: a parallel-guiding mechanism, a projectile launcher, and a deployable chair. This enhanced understanding of stress invariance provides innovative insight into the way devices can be designed for systems that operate across different scales.